Histological and Histochemical Studies on the Lingual Tonsil of the Buffalo (Bubalus bubalis) - Girgiri, Ibrahim Alhaji; Kumar, Pawan (Journal of Buffalo Science, 2019)
The study was conducted on lingual tonsil of six adult buffaloes (5-6 years of age) of the local mixed breed to explore histomorphological characteristics with functional significance. The mucosal surface of the lingual tonsil lined by stratified squamous keratinized epithelium was comprised of strata basale, spinosum, granulosum and corneum whereas towards the deeper folds the epithelium was stratified squamous non-keratinized. The latter epithelium modified into reticular epithelium especially toward the deeper portion and was characterized by a reduced number of epithelial cells, loss of distinct strata and heavy infiltration of lymphoid cells. The propria submucosa had loose irregular connective tissue along with glandular and lymphoid tissue. The lymphoid tissue was mainly distributed in the form of lymphoid follicles and diffused arrangement. The follicles of varying shapes and size showed darkly stained corona and lightly stained germinal centre were surrounded by parafollicular areas. The parafollicular areas possessed high endothelial venules (HEVs) with large sized endothelial cells having round to oval nuclei with distinctly visible centric or eccentric nucleoli. These HEVs are involved in trafficking of lymphocytes by transendothelial and interendothelial migration. The mucous glandular acini presented strong reactions for glycogen, acidic mucopolysaccharides, weakly sulfated mucosubstances, hyaluronic acid, sialomucins and mucins as demonstrated by different histochemical techniques. The secretions of acini also showed the presence of more than 4% content of cysteine. The presence of modified reticular epithelium and associated lymphoid tissue suggested that the lingual tonsil may be involved in sampling of oral antigens and transporting them to the underlying mucosal lymphoid tissue for processing and initiation of immune responses. The future microbiological studies may exploit the tonsil as a targeted organ for improved delivery of existing mucosal vaccines and development of new strategies for oral vaccines.